Konsep Pemaafan Hakim dalam Kitab Undang-Undang Hukum Pidana Ditinjau dari Asas Kepastian Hukum - Lume Hetty Alphani Simbolon; Ismaidar Ismaidar; Abdul Rahman Maulana Siregar; Muhammad Harimanka S Harahap (Lembaga Pengembangan Kinerja Dosen, 2026)
Judicial pardon is one of the significant reforms introduced by Law Number 1 of 2023 concerning the Indonesian Criminal Code, authorizing judges to refrain from imposing criminal punishment or other legal measures even after a defendant has been lawfully proven guilty. Although this concept is intended to promote substantive justice, its regulation raises concerns regarding the limits of its application and the principle of legal certainty. This study aims to analyze the regulation of judicial pardon under the Indonesian Criminal Code, examine its application from the perspective of legal certainty, and formulate an ideal regulatory framework that ensures legal certainty while preserving judicial discretion. This research employed a normative legal research method using statutory and conceptual approaches. Legal materials were collected through library research and analyzed qualitatively using a descriptive-analytical method. The findings indicate that judicial pardon constitutes an integral part of the sentencing guidelines under the Criminal Code, yet its implementation lacks clear normative parameters, potentially resulting in inconsistent interpretation and sentencing disparity. Accordingly, clearer legal standards, implementation guidelines, and more comprehensive judicial reasoning are necessary to achieve a balanced realization of justice, legal certainty, and legal utility within Indonesia's criminal justice system.